Ventilator-associated pneumonia in an adult clinical-surgical intensive care unit of a Brazilian university hospital: incidence, risk factors, etiology, and antibiotic resistance - Rocha,Laura de Andrade da (2008)
The objective of this study was to evaluate clinical characteristics, etiology, and resistance to antimicrobial agents, among patients with ventilator-associated pneumonia (VAP). A case study vs. patients control under mechanical ventilation and hospitalized into clinical-surgical adults ICU of HC-UFU was performed from March/2005 to March/2006. Patients under ventilation for over 48 h were included in the study including 84 with diagnosis of VAP, and 191 without VAP (control group). Laboratory diagnosis was carried out through quantitative microbiological evaluation of tracheal aspirate. The identification of pathogens was performed by classical microbiological tests, and the antibiotics sensitivity spectrum was determined through the CLSI technique. VAP incidence rate over 1,000 days of ventilation was 24.59. The mean (± SD) duration of mechanical ventilation prior to VAP diagnosis was 23.2 ± 17.2 days. By multivariate analysis the risk factors predisposing for VAP were: mechanical ventilation time and mechanical ventilation > seven days, tracheostomy and use of > three antibiotics. Mortality rate was high (32.1 %) but lower than that of the control group (46.5%). Major pathogens were identified in most of patients (95.2%) and included: Pseudomonas aeruginosa (29%), Staphylococcus aureus (26%), Enterobacter/Klebsiella/Serratia (19%) and Acinetobacter spp. (18%), with expressive frequencies of P. aeruginosa (52%), S. aureus (65.4%) and Enterobacteriaceae (43.7%) resistant to imipenem, oxacillin and 3/4 generation cephalosporins, respectively. In conclusion, our observation showed VAPs caused by multiresistant microorganisms, the prescription of > three antibiotics, and mortality with unacceptably high rates. The practice of de-escalation therapy appears to be urgently needed in order to improve the situation.